2005
DOI: 10.1128/iai.73.3.1506-1514.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Membrane Tumor Necrosis Factor Alpha by Gingipains fromPorphyromonas gingivalis

Abstract: Gingipains are cysteine proteinases produced by Porphyromonas gingivalis, a major causative bacterium of adult periodontitis. They consist of arginine-specific (HRgpA and RgpB) and lysine-specific (Kgp) proteinases. Gingipains strongly affect the host defense system by degrading some cytokines, components of the complement system, and several immune cell receptors. In an in vitro model, gingipains were shown to degrade soluble tumor necrosis factor alpha (TNF-␣). However, since membrane TNF-␣ shows strong biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 46 publications
3
65
0
2
Order By: Relevance
“…This suggests that BCAEC are in some way able to protect Ncadherin from cleavage by Kgp activity at later time points in order to counteract the apoptotic signaling and/or stimulate survival signaling. A similar phenomenon was observed in the gingipain-mediated cleavage of TNF-α in fibroblasts, in which HRgpA was shown to have the most activity toward TNF-α, but Kgp-induced cleavage of TNF-α was greatly increased if TNF-α re-expression was prevented, suggesting that the loss of TNF-α through Kgp cleavage could be compensated for by de novo synthesis (128), allowing cells to offset the Kgp-induced effects. Moreover, we have observed that a high concentration of Kgp can cause BCAEC detachment and apoptosis (our unpublished observations) suggesting that there is a threshold level of gingipain activity below which a cell can remain viable, but at gingipain activity above this level the cell cannot overcome gingipain-induced effects and becomes apoptotic.…”
Section: Apoptosis Can Occur With and Without Caspase Involvementsupporting
confidence: 62%
“…This suggests that BCAEC are in some way able to protect Ncadherin from cleavage by Kgp activity at later time points in order to counteract the apoptotic signaling and/or stimulate survival signaling. A similar phenomenon was observed in the gingipain-mediated cleavage of TNF-α in fibroblasts, in which HRgpA was shown to have the most activity toward TNF-α, but Kgp-induced cleavage of TNF-α was greatly increased if TNF-α re-expression was prevented, suggesting that the loss of TNF-α through Kgp cleavage could be compensated for by de novo synthesis (128), allowing cells to offset the Kgp-induced effects. Moreover, we have observed that a high concentration of Kgp can cause BCAEC detachment and apoptosis (our unpublished observations) suggesting that there is a threshold level of gingipain activity below which a cell can remain viable, but at gingipain activity above this level the cell cannot overcome gingipain-induced effects and becomes apoptotic.…”
Section: Apoptosis Can Occur With and Without Caspase Involvementsupporting
confidence: 62%
“…P. gingivalis utilizes a myriad of virulence factors that contribute to chronic periodontitis. Among these are a polysaccharide capsule, fimbriae, proteases for opsonins C3 and IgG, gingipains (21,30,43,52), bacterial lipopolysaccharides (LPS) (22,44), and toxins and hemagglutinins (10,25).…”
mentioning
confidence: 99%
“…Periodontitis is one of the most common inflammatory diseases and is characterized by the presence of (mainly gram-negative) anaerobes, accumulation of immune cells, formation of periodontal pockets, and loss of tooth attachment (1,2). Recent studies have investigated the roles of cytokines and secreted proteinases in periodontitis (3).…”
Section: Introductionmentioning
confidence: 99%